Digital-Based Academic Management Service : A Case Study in Open University - Sarah, Siti; Sugiarto, Sugiarto; Ahmad, Masduki (Jurnal Paedagogy, 2023)
This study aims to analyze the digital-based academic management services for students of the Open University Elementary School Teacher Education study program. This research approach is qualitative with a case study method. The subject of this research is students and the head of the tertiary institution. Data collection was carried out using documents, observations, questionnaires and interviews. Data analysis refers to qualitative research. The results showed that 1) OU's planning management is considered very good for the process of providing the education needed by students. 2) OU coordinates and places the right people in every part needed in the implementation of education at OU so that the academic services provided to students can be maximized and meet student needs. 3) The implementation of OU's service management is carried out by the operational procedures set by OU. OU is developing and improving the quality of management to provide excellent service to students. 4) The evaluation management that OU already has also shown an evaluation process that is systematic and by the procedures owned by OU in providing services to students